The social context in bark beetle – fungus bioassays: a case study in European fir engraver bark beetles and their fungal associates - Tanin, Sifat Munim; Nuotclà, Jon Andreja; Biedermann, Peter H. W. (Frontiers in Microbiology, 2026)
BackgroundCertain species of bark beetles (Curculionidae: Scolytinae) are among the most aggressive herbivorous forest insects due to their mass aggregation behavior and symbiosis with filamentous fungi. These characteristics help them overwhelm the natural defenses of the healthy trees they attack, and consequently, they are classified as primary pest species. Despite their important role in the beetles’ success, the community of fungal symbionts and their key mutualist taxa are only well understood for a few symbionts in a small number of bark beetle species. Recent developments have shown that key mutualists can be identified using in vitro olfactory or gustatory bioassays. However, these assays have only tested mixed-sex groups of beetles. This introduces potential biases compared to individual assays due to the known tendency of these beetles to aggregate.MethodsThis study focuses on the poorly studied fungal symbionts of European fir bark beetles in the genus Pityokteines, specifically P. vorontzowi and P. curvidens. We used a newly developed, two-tier bioassay to evaluate the attraction of beetles to olfactory and gustatory fungal cues in a specific order to identify essential mutualists. Additionally, we are the first to investigate whether testing individual beetles or mixed- or same-sex groups influences the outcome of such bioassays.ResultsOur results show that Pityokteines beetles responded more strongly to physical contact with the fungus than to volatiles alone. Of the five commonly isolated species, only Geosmithia sp. and Ophiostoma piceae were attractive. Females responded to volatile cues, while males did not. Both sexes preferred to bore their feeding tunnels in these two fungi but were repelled by one of the other species, Graphilbum fragrans. The social context significantly impacted the beetles’ behavior: same-sex groups exhibited the strongest response to the offered fungal cues, while mixed-sex groups demonstrated the weakest response.ConclusionIn summary, we identified key fungal species in Pityokteines bark beetles that now need to be assessed individually for their function(s). Most importantly, our results suggest that previous studies should be reassessed because sex and social context must be considered when conducting such bioassays.